Factors influencing quality of life in asthmatics – a case–control study. (24th October 2012) - Al‐kalemji, Abir; Petersen, Karin Dam; Sørensen, Jan; Sherson, David; Thilsing, Trine; Schlünssen, Vivi; Omland, Øyvind; Thomsen, Gert; Bælum, Jesper
Abstract Introduction The quality of life (QOL) in persons with asthma is reduced and different factors such as demography, asthma severity and psychiatric comorbidity play an influential role. However, little is known about the interplay of these factors. Objective To describe QOL in relation to asthma and analyse for the relative impact of asthma severity, psychiatric comorbidity, lifestyle (smoking and obesity) and demographic determinants on QOL in persons with asthma. Methods One thousand one hundred sixty‐one subjects from an earlier cohort with and without asthma were sent an asthma screening questionnaire and a generic QOL measuring instrument (15D). Results Seven hundred seventy‐eight valid responses (67%). QOL was significantly reduced in persons with asthma compared with controls (P = 0.001), almost on all domains of 15D. In the adjusted regression model, asthma severity, depression, female gender and smoking were associated with reduced QOL, suggesting that these factors play an independent role on lowering QOL. Depression did not inflate the relationship between asthma severity and worse QOL, suggesting that asthma severity plays an independent role on everyday life regardless of psychological state. Conclusion Asthma severity, psychiatric comorbidity, female gender and smoking were identified in this study to be major contributors to decreased QOL in asthmatics. Health professionals should be aware of this complex picture and take these factors into consideration when choosing the proper treatment of asthma patients. Asthma, asthma severity, epidemiology, psychiatric comorbidity, QOL.